ANÁLISE DE UM PRÉDIO CERTIFICADO LEED - NOVAS CONSTRUÇÕES NA VERSÃO ATUAL DA CERTIFICAÇÃO DE OPERAÇÃO E MANUTENÇÃO - Canazaro, Camila Copello; Kern, Andrea Parisi (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The rational use of materials in the construction industry and the responsibility this sector has towards the environment has been object of research in the academia over the past few decades. Environmental certifications emerged in this scenario to guide those involved in the process to reduce the environmental impacts caused by the sector. In this context, the operation and maintenance of the building can also contribute to reduce the impacts on the environment and base the analyzes of the LEED certification carried out in this study. The main goal of this essay is to verify that a building, already certified in LEED NC v3 (2009), would meet the requirements of the LEED EBOM v4 (2016) version. This analysis showed significant changes in the certification. The building achieved 82 points on the operations and maintenance certification, reaching the Platinum category, despite the lower score on the design certification, due to the practices required by the program already being performed by its operators.